PAKELIRAN WAYANG BETEL INOVATIF SIWARAJANI: PENCIPTAAN WAYANG DON NANGKA BERBASIS LAKON LUBDHAKA SIWARATRI KALPA - ida bagus arthya weda singarsa; I Gusti Putu Sudarta; I Dewa Ketut Wicaksana (JURNAL DAMAR PEDALANGAN, 2026)
This artistic creation aims to develop an innovative wayang (shadow puppet) performance entitled Siwarajani, based on the Lubdhaka story from the Siwaratri Kalpa text, utilizing wayang don nangka (jackfruit leaf puppets) as the primary medium. The work addresses the gap between the ideal preservation of Balinese pedalangan tradition and contemporary artistic expression, while integrating ecological awareness and philosophical depth into performance art. The creation process employs the Panca Sthiti Ngawi Sani methodology developed by I Wayan Dibia, encompassing five stages: ngawirasa (inspiration), ngewacak (exploration), ngarencana (conception), ngawangun (execution), and ngebah (presentation). This method provides a structured framework for transforming abstract spiritual concepts into tangible artistic expression. The result is a 47-minute integrated performance that harmoniously combines traditional pedalangan elements with digital media innovation. The wayang don nangka crafted from dried jackfruit leaves serves not merely as visual property but as a philosophical symbol representing life cycles, impermanence, and spiritual transformation. The performance demonstrates that everyday natural materials, often overlooked, can become meaningful artistic media. This work implies significant potential for future research in developing sustainable puppet media and integrating digital platforms to support wayang performances. The novelty of this creation lies in the transformation of dried jackfruit leaves into philosophically grounded puppet media integrated with digital visual performance.